Age-related macular degeneration: Prevalence and risk factors - a cross-sectional study : The Tromsø Study 2007/2008 - Erke, Maja Gran (University of Tromsø, 2013)
The papers of this thesis are not available in Munin: 1. Bertelsen G, Erke MG, von Hanno T, Mathiesen EB, Peto T, Sjølie AK and Njølstad I.: 'The Tromsø Eye Study: study design, methodology and results on visual acuity and refractive errors', Acta Ophthalmologica (2012), Online before print. Available at http://dx.doi.org/10.1111/j.1755-3768.2012.02511.x 2. Erke MG, Bertelsen G, Peto T, Sjølie AK, Lindekleiv H and Njølstad I.: 'Prevalence of Age-Related Macular Degeneration in Elderly Caucasians: The Tromsø Eye Study', Ophthalmology (2012), vol.119(9):1737–1743. Available at http://dx.doi.org/10.1016/j.ophtha.2012.03.016 3. Erke MG, Bertelsen G, Peto T, Sjølie AK, Lindekleiv H and Njølstad I.: 'Cardiovascular risk factors associated with agerelated macular degeneration: The Tromsø Study' (manuscript) 4. Erke MG, Bertelsen G, Peto T, Sjølie AK, Lindekleiv H and Njølstad I.: 'Lactation, female hormones and age-related macular degeneration: The Tromsø Study' (manuscript) Age-related macular degeneration (AMD) is an important cause of visual impairment and blindness worldwide. The number of people affected by the disease is expected to rise due to increasing longevity. Development of adequate eye care for these patients should be based on knowledge about the prevalence of AMD. Further, preventive measures are the best strategy for any disease. The aims of this thesis were to estimate the prevalence of AMD and examine risk factors associated with AMD. We described prevalence rates of AMD among Caucasian elderly participants from the Tromsø Eye Study, a population-based study in Norway. The overall prevalence of late AMD was 3.5 % among the participants aged 65-87 years old. Neovascular AMD outnumbered geographic atrophy. Symmetry between eyes was relatively low. Prevalence increased strongly with age. No significant sex differences in prevalence rates of AMD were observed. Refractive error was lower in eyes with late AMD than in eyes without late AMD. We then analysed relationships between traditional ...